Answer:
Explanation:
so we know 3w = L + 5
and then we know that 2w + 2L = 194
so those are our two equations
since we have L by itself in the first equation, we are going to move the 5
L = 3w - 5
so now we can plug that in as L in the second equation
2w + 2(3w - 5) = 194
so now we distribute that 2
2w + 6w - 10 = 194
then simplify
8w - 10 = 194
then add the 10 to the other side
8w = 204
then we divide the 8
we get w = 25.5
so now we take that and go all the way back and plug that into the othr equation (ik this is a lot)
L = 3w - 5
so we plug in what we got for w
L = 3(25.5) -5
then multiply
L = 76.5 - 5
L = 71.5
so we end up with
w = 25.5 and L = 71.5
have a great day!! <3